1998
DOI: 10.1073/pnas.95.23.13397
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of medium-chain-length polyhydroxyalkanoates inArabidopsis thalianausing intermediates of peroxisomal fatty acid β-oxidation

Abstract: Polyhydroxyalkanoate (PHA) is a family of polymers composed primarily of R-3-hydroxyalkanoic acids. These polymers have properties of biodegradable thermoplastics and elastomers. Medium-chain-length PHAs (MCLPHAs) are synthesized in bacteria by using intermediates of the ␤-oxidation of alkanoic acids. To assess the feasibility of producing MCL-PHAs in plants, Arabidopsis thaliana was transformed with the PhaC1 synthase from Pseudomonas aeruginosa modified for peroxisome targeting by addition of the carboxyl 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 38 publications
6
101
0
2
Order By: Relevance
“…The yields in the two transgenic lines analysed, were 0.017 mg and 0.26 mg of polymer/g of cell dry weight (Table 1). Transgenic A. thaliana expressing the mcl-PHA-polymerase in the peroxisomes accumulated similar amounts of mcl-PHAs in leaves (0.2 mg/g of cell dry weight) and 20 times more polymer (4 mg/g of cell dry weight) in germinating seedlings (Mittendorf et al 1998). The monomer composition of the polymer accumulated in the two transgenic potato lines analysed in the present report is shown in Table 1 and consisted of 3-(R)-hydroxyalkanoates with carbon chains ranging from C-6 to C-12.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The yields in the two transgenic lines analysed, were 0.017 mg and 0.26 mg of polymer/g of cell dry weight (Table 1). Transgenic A. thaliana expressing the mcl-PHA-polymerase in the peroxisomes accumulated similar amounts of mcl-PHAs in leaves (0.2 mg/g of cell dry weight) and 20 times more polymer (4 mg/g of cell dry weight) in germinating seedlings (Mittendorf et al 1998). The monomer composition of the polymer accumulated in the two transgenic potato lines analysed in the present report is shown in Table 1 and consisted of 3-(R)-hydroxyalkanoates with carbon chains ranging from C-6 to C-12.…”
Section: Discussionmentioning
confidence: 99%
“…The same was observed in mcl-PHAs accumulated in natural or recombinant prokaryotes (Table 1). In contrast, when b-oxidation intermediates were directed into mcl-PHA biosynthesis in natural hosts (De Waard et al 1993), recombinant yeast (Poirier et al 2001 or recombinant A. thaliana (Mittendorf et al 1998(Mittendorf et al , 1999Allenbach and Poirier 2000), the monomer composition also included unsaturated monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches were tested to produce mclPHAs in plants (Figure 4). Using the 3-hydroxyacyl-CoA intermediates generated in the peroxisome by the fatty acid b-oxidation pathway, a mclPHA consisting of C6-C16 monomers was produced to a level of 0.4% dry weight in A. thaliana seedlings (Mittendorf et al, 1998). These polymers consisted of more than 40-50 mol% C12 and longer monomers, and also contained a significant amount of unsaturated monomers.…”
Section: Polyhydroxyalkanoatesmentioning
confidence: 99%
“…Conversely, coupling GC to mass spectrometry detector (GC-MS) ensures more reliable detection, identity confirmation and quantification of PHA monomers, as well as enables tentative identification of novel PHA monomers in the absence of analytical standards [133]. Figure 4 shows representative GC-MS chromatograms of PHA monomers [37]. A recent study by Tan et al [132] showed that PHA monomers with carbon number between 4 and 16 have strong linear correlations with their respective retention times and response factors (R 2 ≥ 0.987) under GC-MS, which enabled the retention time and response factor of other PHA monomers to be predicted.…”
Section: Quantification and Characterization Of Pha In Biomassmentioning
confidence: 99%